Assessment of crop loss in Arabica coffee due to white stem borer, Xylotrechus quadripes Chevrolat (Coleoptera: Cerambycidae) infestation - Kumar, A. Roobak; Gopinandhan, T. N.; Krishna Reddy, P.; Uma, M. S.; Patil, Somashekhargouda; Manjunath Reddy, G. V.; Seetharama, H. G. (Journal of Plantation Crops, 2020)
The coffee white stem borer (CWSB) is the most dreaded pest of Arabica coffee in India. Due to the concealed nature of this pest, the management measures are difficult and require the timely implementation of control measures. The recommended practices for the management of CWSB mainly targets on eggs and early instar larvae, apart from tracing and uprooting of infested plants before the commencement of flight periods (April-May and Oct-Dec). In general, youngArabica coffee plants infested by CWSB die within a year, whereas aged plants withstand the attack for few more years. However, such plants become less productive, susceptible to diseases and also serve as inoculum for further spreading of the infestation. A study was undertaken to assess the crop loss due to CWSB infestation on established Arabica plantation in Tamil Nadu. The result indicated a significant difference between healthy and infested plants and the crop loss was to the tune of 17.7 per cent. Further, quantitative data on out-turn percentages recorded at different stages of coffee processing (right from harvesting of fruits to marketable green coffee bean) are discussed in this paper.